PELATIHAN PENGEMBANGAN SOFT SKILLS MAHASISWA DALAM MENGHADAPI TANTANGAN BERORGANISASI - Ramadhania, Sherin; Abid, Muhammad Miftahul; Suroso, Muhammad Suryo Panotogomo Abi; Permata, Nia Sastra (LPPM Universitas Bina Bangsa, 2024)
In the rapidly accelerating era of globalization, soft skills have become crucial elements required by university graduates, alongside hard skills. Soft skills such as leadership, time management, self-management, and group management are essential in both the professional world and organizational settings. In the Industrial Engineering Student Association (HMTI) at the Institut Teknologi Sumatera (ITERA), many students still face challenges in developing these essential soft skills. Therefore, a structured and continuous soft skills development training program is necessary. This community service activity was conducted by the lecturers of Industrial Engineering at ITERA using coaching and simulation games to equip students with relevant soft skills for managing the organization. The coaching method was used to provide direct guidance, while simulation games were applied to train communication skills, decision-making, and problem-solving in real-life scenarios. The training proved to be effective in enhancing students' leadership, time management, and self-management abilities, as well as helping them face challenges in organizational and professional settings. The PDCA (Plan, Do, Check, Action) cycle was also implemented to evaluate and improve the organizational processes. The conclusion of this activity is that the development of soft skills plays a significant role in the success of student organizations and future careers. Several recommendations are provided to enhance the effectiveness of future training, including aligning the training materials with the specific needs of organizations and collaborating with professionals from various industries